The Ease of Language Understanding (ELU) model: theoretical, empirical, and clinical advances - Rönnberg, Jerker; Lunner, Thomas; Zekveld, Adriana; Sörqvist, Patrik; Danielsson, Henrik; Lyxell, Björn; Dahlström, Örjan; Signoret, Carine; Stenfelt, Stefan; Pichora-Fuller, M. Kathleen; Rudner, Mary (Frontiers in Systems Neuroscience, 2013)
Working memory is important for online language processing during conversation. We use it to maintain relevant information, to inhibit or ignore irrelevant information, and to attend to conversation selectively. Working memory helps us to keep track of and actively participate in conversation, including taking turns and following the gist. This paper examines the Ease of Language Understanding model (i.e., the ELU model, Rönnberg, 2003; Rönnberg et al., 2008) in light of new behavioral and neural findings concerning the role of working memory capacity (WMC) in uni-modal and bimodal language processing. The new ELU model is a meaning prediction system that depends on phonological and semantic interactions in rapid implicit and slower explicit processing mechanisms that both depend on WMC albeit in different ways. A revised ELU model is proposed based on findings that address the relationship between WMC and (a) early attention processes in listening to speech, (b) signal processing in hearing aids and its effects on short-term memory, (c) inhibition of speech maskers and its effect on episodic long-term memory, (d) the effects of hearing impairment on episodic and semantic long-term memory, and finally, (e) listening effort. New predictions and clinical implications are outlined. Comparisons with other WMC and speech perception models are made.